Progress of application of Traditional Chinese Medicine nursing in elderly patients with osteoporosis (中医护理在老年骨质疏松症患者中的应用进展) - LI Cheng (李成); TANG Ling (唐玲); ZHOU Hongyue (周红悦) (Association of Integrative Nursing, 2022)
Osteoporosis affects elderly people's quality of life, which has become great concern of the society as fastest-growing aging population. This paper analyzed the potential reasons of osteoporosis in the elderly from the perspective of Traditional Chinese Medicine (TCM), and reviewed the studies about TCM dietary therapy, exercise guidance, emotional care in elderly patients with osteoporosis, in order to provide reference for promoting healthy lifestyle and reliving clinical symptoms in elderly patients with osteoporosis. (骨质疏松症严重影响老年人生活质量, 随着人口老龄化趋势加重, 已然成为社会关注的焦点。本文从中医角度分析老年骨质疏松症的病因, 总结中医食疗、运动指导和情志护理等措施在老年骨质疏松症患者中的应用现状, 旨在为促进患者养成健康的生活方式、缓解疾病症状提供参考。)